Usage of Internet in Academic Endeavors of University Students in Kathmandu, Nepal (People's Journal of Management, 2024)
The study aims in analyzing the use of internet in academic success of university students. The study has adopted survey research design. The convenience sampling method is used to collect the response from science, law and management students from different university. The total usable response is confined to hundred samples. The descriptive, Chi-square test, F-test and correlation analysis are conducted using SPSS software in the study. The analysis has found that male uses internet for communication purpose better than that of female students. NTC is found mostly preferred internet service provider for the respondents of education background. The analysis further concluded that there is no significant difference between the education background and the use of internet for doing assignment, social networking, entertainment and communication. However, there is no significant difference between faculty selected by students and choice of internet browsing speed. There is no significant association between pressure group and type of faculty chosen by students, although science students are more sensitive towards pressure group. There is no significant relationship between occupation of students’ guardian and preferred ISP. There is significant difference between type of ISP and level of satisfaction of respondents. The study revealed that there is no significant relationship between type of ISP subscribed and payment system. The study has found no significant relationship between amount charged and ISP subscribed. There is no significant relationship between overall performance and ISP subscribed. The study concluded that there is significant relationship between ISP subscribed and switching option of ISP. Finally, it is concluded that the use of internet in academic endeavor become essential in recent years. Thus, policy makers, service providers and university should develop a framework that can integrate their curriculum to go along with information and technology.